Parallel Platformization of Health: Health Communication on Douyin and TikTok - Li, Xinna (AoIR Selected Papers of Internet Research, 2026)
This study examines the parallel platformization of health by analyzing how verified healthcare professionals present themselves and disseminate medical information on Douyin and TikTok. Through content analysis of videos published by 10 popular verified doctors on each platform and homepage analysis, as well as policy analysis of platform regulations on the healthcare industry, this study explores how platform infrastructure, business models, and governance influence the roles, interactions, and communication styles of healthcare professionals on Douyin and TikTok.